Penerapan Teknik Anyaman dengan Kombinasi Denim Bekas dan Macramé pada Pembuatan Hoodie Jacket - Adzkia Bintang Lailatus Zahra; Edi Suwasana (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
This research aims to examine the application of weaving techniques combined with macrame in making hoodie jackets made from used denim, as an effort to support sustainable fashion. The background of this research is the increase in textile waste, especially used denim, which has not been maximally utilized. The method used is Research and Development (R&D), with the stages of design design, making samples of woven techniques, validation by experts, and making prototypes. The technique applied was two-axis plaiting combined with macrame knots using braided cotton rope. The results showed that the combination of these two techniques could be effectively applied to the hoodie jacket structure. The resulting prototype proved to be functional, comfortable to wear, and has high aesthetic value. This research is in line with previous findings such as Syaani (2020), which showed the role of webbing as a structural and decorative element, as well as Tiara Lugina (2015) and Mayarani (2019), which highlighted the visual strength of traditional techniques in modern fashion. Based on the results of the research, it is suggested that pressing of the seams is done before turning to prevent thickening, and macrame knots are locked on the lining to make it more stable. The results of this study show that the combination of webbing and macrame with used denim is effectively applied in the design of an innovative and environmentally friendly jacket.